Distinct Roles of Met and Interacting Proteins on the Expressions of takeout Family Genes in Brown Planthopper - Lin, Xinda; Zhang, Ling; Jiang, Yanyun (Frontiers in Physiology, 2017)
The takeout family genes encode relatively small proteins that are related to olfaction and are regulated by juvenile hormone (JH). The takeout genes modulate various physiological processes, such as behavioural plasticity in the migratory locust Locusta migraloria and feeding and courtship behaviours in Drosophila. Therefore, to understand the regulatory mechanism of these physiological processes, it is important to study the expressions of the takeout genes that are regulated by JH signalling. We used quantitative real-time PCR (qRTPCR) to study the role of JH signalling in the regulation of the takeout family genes in the brown planthopper Nilaparvata lugens (N. lugens) through the application of Juvenile hormone III(JHIII) and the down-regulation of key genes in the JH signalling pathway. The topical application of JHIII induced the expressions of most of the takeout family genes, and their expressions decreased 2 and 3 days after the JHIII application. Down-regulating the brown planthopper JH receptor NlMethoprene-tolerant (NlMet) and its interacting partners, NlTaiman (NlTai) and Nlß-Ftz-F1 (Nlß-Ftz), through RNAi, exhibited distinct effects on the expressions of the takeout family genes. The down-regulation of NlMet and NlKrüppel-homologue 1 (NlKr-h1) increased the expressions of the takeout family genes, while the down-regulation of the Met interacting partners NlTai and Nlß-Ftz decreased the expressions of most of the takeout family genes. This work advanced our understanding of the molecular function and the regulatory mechanism of JH signalling.